Androgen deprivation therapy and the risk of subsequent keratitis - Dai-Wei Liu; Ren-Jun Hsu; Sheng-Yao Huang; Yen-Hsiang Liao; Chen-Ta Wu; Wen-Lin Hsu (Tzu Chi Medical Journal)
Objectives: The objective of the study was to determine the risk of subsequent keratitis in prostate cancer (PCa) patients treated with androgen deprivation therapy (ADT). Materials and Methods: Three thousand three hundred and nine patients with PCa were identified using data from Taiwan’s National Health Insurance Research Database for 2001 through 2013. Among those patients, 856 treated with ADT comprised the study group, while 856 non-ADT-treated patients matched with 1:1 propensity-score-matched analysis comprised the control group. The demographic characteristics and comorbidities of all the patients were analyzed, and Cox proportional hazards regression was utilized to determine the hazard ratios (HRs) for subsequent keratitis. Results: A total of 157 (9.2%) patients had newly diagnosed keratitis. Compared to the non-ADT-treated patients, the ADT-treated patients had a reduced risk of subsequent keratitis, with an adjusted HR of 0.38 (95% confidence interval: 0.27–0.55; P < 0.001). Conclusion: ADT treatment apparently decreased the risk of subsequent keratitis in the investigated PCa patients, but the clinical significance of this finding should be further assessed in additional studies.